Lessons learnt from a comparative examination for strata dispute resolutions: Singapore, British, Columbia and Malaysia - Mohamad, Nor Asiah (2014)
Purpose: The objective of this paper is to report the early findings of a research titled “An Exploratory Study of Strata Dispute Resolution in Malaysia”. Secondly, to look at various ways disputes are handled in strata management. Methodology/Approach: This paper discusses various cross- jurisdictional approaches, reviews the scope, analyses their legal frameworks and examines lessons learnt regarding the implementation of various mechanisms of alternative dispute resolution. Findings: The study reveals that alternative dispute resolution (ADR) mechanisms are widely utilised in strata management in many jurisdictions despite having statutory body to handle dispute. The ADR mechanisms are either made compulsory or voluntary within or outside adjudication system. It is also showed that strata comparative studies are considerably understudied. The paper contributes by addressing some of the pertinent issues, which are current and timely.